Fiscal Stimulus Packages and Uncertainty in Times of Crisis – The Option of Waiting Can Be Valuable, Though! - Ansgar Belke (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2009)
Policymakers in the EU member states are currently shaping rescue packages to prevent the financial crisis hitting their economies with unmitigated force. Each government is responding to the emerging problems with a country-specific set of measures. Given the global nature of the crisis, would coordinated action at the European level not be a better approach? Was the German government - much-criticized for its initial reluctance to adopt massive fiscal stimulation measures - right after all to exploit the option value of waiting in a situation of high uncertainty? The answer to the second question is a qualified yes. However, the answer to the first one is more complex and crucially depends on how reasonable it appears to model the impact of the economic crisis as an exogenous demand shock which has hit the euro area countries.
Keywords: E62; F42; H62; 330; Policy co-ordination; fiscal multiplier; fiscal stimulus package; liquidity constraint; option value of waiting; uncertainty; Finanzmarktkrise; Internationaler Finanzmarkt; Antizyklische Finanzpolitik; Internationale wirtschaftspolitische Koordination; Dauer; Entscheidung bei Unsicherheit; Realoption; Wirtschaftspolitische Wirkungsanalyse; EU-Staaten